How Spanish Multinationals implement CSR in Latin American countries: a focus on the energy sector - Llera Bagüés, Maria (2009)
Spain is behind in the level of CSR implementation in comparison with other European countries, among other reasons due to low political commitment and support. In fact, private companies and in particular large corporations and multinationals are fostering the CSR arena in Spain, and despite the difficulties at home, the Spanish multinationals try to export their CSR initiatives abroad. Here, the energy sector is used as a guiding tool for the analysis due to the dominant position of the Spanish energy multinationals in the Latin American market. Therefore, the aim of this study is to explore the main reasons which motivate the Spanish energy multinationals to implement their CSR strategies in their Latin American subsidiaries and which issues must be taken into consideration.